Pengaruh Kedalaman Rhizofer Tanaman Melati Air (Echinodorus palaefolius) Terhadap Kuantitas Oksigen Terlarut Pada Sistem Sub Surface Vertical Flow Constructed Wetland - Mona Loshinta; Haryati Bawole Sutanto; Guruh Prihatmo (Universitas Katolik Musi Charitas, 2020)
Melati air has aerenchyma which plays an important role in the process of transferring oxygen to the rhizofer to qualify the oxygen demand in constructed wetland system. In this research, the Sub Surface Vertical Flow Constructed Wetland (SSVF CW) system was built to determine the effect of the depth of the Echinodorus palaefolius's rhizofer on the quantity of dissolved oxygen (DO) in the SSVF CW system. This system was designed to treat domestic wastewater with HRT of 4 days. SSVF CW was built using soil and stones of 1-2 cm, 2.5-5 cm, 7-10 cm as media. This study shows that melati air with an average root length of 47.25 cm and the longest root of 60 cm was able to influence DO concentration in the system. The removal efficiency of TSS, BOD, total ammonia, and phosphate was 93,48%, 89,39%, 59,39%, and 66,53% respectively. Whereas nitrate and TDS didn't decrease which could be possible due to the well running of nitrification process.